Cement stabilized crushed stone mixed material and preparation method thereof

By introducing modification enhancer and optimizing proportions into cement-stabilized gravel mixed materials, the problems of high dry shrinkage coefficient, prone to cracks and insufficient strength of traditional materials are solved, and the mechanical properties of the materials are improved and durability extended.

CN118754542BActive Publication Date: 2025-04-25宁夏交通建设股份有限公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410799585.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-04-25
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

Traditional cement-stabilized gravel mixed materials have problems such as high dry shrinkage coefficient, easy to produce cracks and insufficient strength, especially when using recycled aggregates, the workingability and strength development of the materials are affected.

Method used

By introducing a modification enhancer, the ratio of the grading of aggregates and the amount of cement is optimized, and the mixing is carried out using a vibrating mixer to reduce the dry shrinkage coefficient and improve the compressive strength and splitting strength.

Benefits of technology

It significantly reduces the dry shrinkage coefficient of cement-stabilized gravel mixed materials, improves its mechanical properties and durability, reduces the risk of cracking of the material during drying, and extends the service life of the road.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004902964000000111
    Figure BDA0004902964000000111
  • Figure BDA0004902964000000121
    Figure BDA0004902964000000121
Patent Text Reader

Abstract

The invention discloses a cement-stabilized crushed stone mixed material and a preparation method thereof, and belongs to the field of construction technology. The mixed material is mixed by aggregate, cement, recycled fine aggregate, polycarboxylic acid water-reducing agent, modified reinforcing agent and water. The aggregate is a mixture of limestone, basalt and recycled coarse aggregate, and the recycled fine aggregate comes from crushed concrete or bricks. The preparation method of the invention comprises mixing the raw materials in a vibrating mixer, paving, rolling and compacting to form a base layer, and covering and maintaining the base layer with a geotextile. Compared with the prior art, the invention effectively reduces the shrinkage coefficient of the mixed material by adding a modified reinforcing agent, and at the same time significantly improves the compressive strength and splitting strength, thereby enhancing the stability and durability of the road base layer. In addition, the invention also promotes the recycling of construction waste, and has significant environmental protection and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of construction, and in particular to a cement-stabilized crushed stone mixed material and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization and the continuous expansion of infrastructure construction, the demand for building materials is growing. Especially in road engineering, cement-stabilized crushed stone mixed materials, as an important base material, are widely used due to their good mechanical properties and stability. However, traditional cement-stabilized crushed stone mixed materials have some limitations, such as high shrinkage coefficient, which easily leads to cracks, affecting the service life of the road and driving safety.

[0003] In the existing technology, researchers and engineers have taken a variety of measures to improve the performance of cement-stabilized crushed stone mixed materials. For example, by optimizing the gradation of aggregates, adjusting the ratio of cement and water, adding different types of water reducers and reinforcing agents, etc. Although these methods have improved the performance of the materials to a certain extent, there is still room for improvement, especially in reducing the shrinkage coefficient and improving the early strength.

[0004] In addition, with the increasing awareness of environmental protection, how to effectively utilize industrial waste and construction waste has become an important research direction in the field of building materials. The use of recycled aggregates can not only reduce the impact of waste on the environment, but also reduce material costs and achieve sustainable utilization of resources.

[0005] However, the introduction of recycled aggregates may also bring some technical challenges, such as the activity of recycled fine aggregates may be lower than that of natural fine aggregates, which may affect the workability and strength development of cement-stabilized crushed stone mixed materials. Therefore, the development of new modified reinforcing agents to improve the interface properties of recycled aggregates and improve the overall performance of mixed materials has become a technical problem that needs to be solved urgently.

[0006] China's invention patent CN103408823B discloses a cement-stabilized macadam base material, its preparation method and asphalt pavement, which relate to the field of building materials technology. The raw materials of the cement-stabilized macadam base material include 70-85 parts of aggregate, 4-5.5 parts of cement, 15-30 parts of recycled fine aggregate and 4-5.5 parts of water; wherein the recycled fine aggregate is a powder with a particle size of 0-3mm obtained by separating the milling material of the asphalt pavement from the oil stone. The preparation method of the cement-stabilized macadam base material, which mixes the raw materials of the above-mentioned cement-stabilized macadam base material, and uses the recycled fine aggregate obtained by petroleum separation to significantly improve the crack resistance of the cement-stabilized macadam, and the asphalt pavement obtained by paving the prepared cement-stabilized macadam has good crack resistance. However, the base material prepared by the invention still has poor mechanical properties and stability, and a high shrinkage coefficient, which easily leads to the formation of cracks, affecting the service life and driving safety of the road. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention introduces a modifying enhancer to effectively reduce the shrinkage coefficient of the cement-stabilized crushed stone mixture and significantly improve its mechanical properties, thereby solving the problem of traditional materials being prone to cracks and insufficient strength.

[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0009] A method for preparing a cement-stabilized crushed stone mixed material is as follows:

[0010] Aggregate, cement, recycled fine aggregate, polycarboxylic acid water-reducing agent, modified reinforcing agent and water are mixed and blended in a vibrating mixer. The mixed material is spread on the location to be paved, rolled and compacted to form a base layer, the base layer is covered with a geotextile, watering is performed every other day to keep the base layer moist, and the base layer is cured to obtain a mixed material.

[0011] The weight proportions of the components are 70-90 parts of aggregate, 4-6 parts of cement, 15-25 parts of recycled fine aggregate, 1-3 parts of polycarboxylic acid water reducer, 2-4 parts of modifier and enhancer and 6-10 parts of water.

[0012] The aggregate is prepared by mixing limestone, basalt and recycled coarse aggregate in a mass ratio of 1-3:0.5-2:3-5. The recycled coarse aggregate is obtained by crushing stone processing waste and passing through a 5-20 mesh sieve.

[0013] The recycled fine aggregate is crushed concrete or bricks, which is obtained by crushing and screening through a 50-200 mesh sieve.

[0014] The mixing time is 5 to 15 seconds, the amplitude of the vibration shaft is 0.5 to 2 mm, and the rotation speed is 150 to 250 rad / s.

[0015] The curing time is 7 to 15 days.

[0016] The preparation method of the modified reinforcing agent is as follows, in parts by weight:

[0017] S1: 0.5-2 parts of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 5-7 parts of ethylene glycol dimethacrylate are mixed and added to 13-17 parts of 2-fluoroacryloyl chloride, nitrogen is introduced to replace the air in the reaction system, 0.08-0.15 parts of initiator are added, and the mixture is heated to 70-90° C. and reacted for 1-3 hours to obtain a pretreated product;

[0018] S2: Add 15 to 17 parts of fumaramide and 70 to 90 parts of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.08 to 0.15 parts of initiator, and react at 70 to 90° C. for 4 to 6 hours to obtain a reactant; wash the reactant with an organic solvent to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0019] The initiator is benzoyl peroxide.

[0020] The organic solvent is one of acetone, anhydrous ethanol and N,N-dimethylacetamide.

[0021] A cement-stabilized crushed stone mixed material is prepared by adopting the preparation method.

[0022] In the present invention, the functions of each substance are as follows:

[0023] Aggregate is the main component of cement stabilized crushed stone mix, providing the skeleton and strength of the structure. The mixture of limestone, basalt and recycled coarse aggregate provides good mechanical properties and durability.

[0024] Cement acts as a binder, reacting with water to form cement paste, which envelops the aggregate and fills the voids, providing adhesion and ultimate strength.

[0025] Recycled fine aggregate is obtained by screening crushed concrete or bricks, which can improve the density and adhesion of the mixture and promote the recycling of resources.

[0026] Polycarboxylate superplasticizers are used to reduce the water usage of cement paste while maintaining or improving workability, thereby improving the strength and durability of the mix.

[0027] The modifying reinforcing agent is a key component of the present invention, which is prepared by a special chemical reaction and is used to improve the mechanical properties and durability of the mixed material.

[0028] Water is a necessary condition for cement hydration reaction. Appropriate amount of water ensures the fluidity and workability of cement paste.

[0029] In the modified reinforcing agent, 1-allyl-1,4-dihydro-3-pyridinecarbonitrile is a part of the modified reinforcing agent. It may help to form a stable polymer network and improve the adhesion and flexibility of the material due to its structural characteristics.

[0030] In the modified enhancer, ethylene glycol dimethacrylate is used as a copolymer monomer and copolymerized with 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and other components to form the main structure of the modified enhancer.

[0031] In the modified enhancer, 2-fluoroacryloyl chloride acts as a reactive monomer and participates in the polymerization reaction. The introduction of fluorine atoms may increase the chemical stability and weather resistance of the polymer.

[0032] In the modified enhancer, benzoyl peroxide is used as an initiator to start the polymerization reaction and promote the connection between monomers to form long-chain polymers.

[0033] Fumaramide, as a part of the modified reinforcing agent, may help to improve the toughness of the polymer and its compatibility with cement due to its structural characteristics.

[0034] In the modifier enhancer, acetone is used to clean the reactants, remove impurities and unreacted raw materials, and ensure the purity and performance of the modifier enhancer.

[0035] Through the synergistic effect of these substances, the cement-stabilized crushed stone mixed material of the present invention aims to achieve excellent mechanical properties, durability and construction performance, while promoting the recycling of construction waste, and has environmental and economic benefits.

[0036] Compared with the prior art, it has the following beneficial effects:

[0037] 1) The present invention aims to improve the performance of cement-stabilized crushed stone mixed materials by adding a modifier. The addition of the modifier may improve the mechanical properties of the mixed material, such as compressive strength and splitting strength, and also help to reduce the drying shrinkage coefficient of the mixed material, which can reduce the risk of cracking of the material during the drying process and improve its durability.

[0038] 2) The present invention uses recycled coarse aggregate and recycled fine aggregate, which promotes the recycling of construction waste and reduces the exploitation of natural resources and the impact on the environment.

[0039] 3) The present invention may improve the overall quality of the project and extend the service life of the road by adding a modified reinforcing agent and optimizing the mix ratio. DETAILED DESCRIPTION

[0040] Main sources of substances:

[0041] Limestone: Lingshou County Woyang Mineral Products Processing Plant, item number: 008.

[0042] Basalt: Lingshou County Junheng Mineral Products Co., Ltd., item number: JH-48.

[0043] Cement: Weishuo Building Materials Business Department, Wuqing District, Tianjin, Cement: PSA32.5.

[0044] Polycarboxylate water reducer: Laiwu Yanhui Building Materials Co., Ltd., item number: 12.3.

[0045] Ethylene glycol dimethacrylate: CAS number: 97-90-5.

[0046] 1-Allyl-1,4-dihydro-3-pyridinecarbonitrile: CAS: 285553-70-0.

[0047] Glycidyl methacrylate: CAS number: 106-91-2.

[0048] Methyl 2-(hydroxymethyl)acrylate: CAS No.: 15484-46-5.

[0049] Methyl methacrylate: CAS number: 80-62-6.

[0050] 2-Fluoroacryloyl chloride: CAS number: 16522-55-7.

[0051] Acryloyl chloride: CAS number: 814-68-6.

[0052] Cinnamamide: CAS number: 621-79-4.

[0053] Methacrylamide: CAS number: 79-39-0.

[0054] 4-Chlorocinnamamide: CAS number: 18166-64-8.

[0055] Acrylamide: CAS number: 79-06-1.

[0056] Benzoyl peroxide: CAS number: 94-36-0.

[0057] The design ideas of the present invention mainly include the following aspects:

[0058] The use of recycled coarse aggregate and recycled fine aggregate, which are obtained from stone processing waste and crushed concrete or bricks after screening, helps to reduce waste accumulation and environmental impact, while saving natural resources.

[0059] By adding modified reinforcing agents, the performance of cement-stabilized crushed stone mixed materials is improved, such as reducing the shrinkage coefficient, increasing the compressive strength and splitting strength, thereby improving the durability and stability of the material.

[0060] In the preparation process of the modifier, specific chemicals (such as 1-allyl-1,4-dihydro-3-pyridinecarbonitrile, ethylene glycol dimethacrylate, 2-fluoroacryloyl chloride, etc.) are selected for reaction to form an effective modifier. These chemicals are selected based on their ability to provide the required physical and chemical properties. The smooth progress of the reaction and the quality of the product are ensured by precisely controlling the reaction conditions (such as temperature, time, nitrogen protection, etc.). The reactants are cleaned with acetone to remove impurities and unreacted raw materials to ensure the purity and quality of the modifier, thereby ensuring the stability and reliability of the final product.

[0061] While ensuring the improvement of material performance, cost-effectiveness is considered, industrial by-products or waste are used as raw materials, reducing the impact on the environment and reducing production costs.

[0062] In summary, the design concept of the present invention is to comprehensively consider multiple factors such as environmental protection, resource recycling, performance improvement, chemical composition optimization, process control and quality assurance, so as to achieve a method for preparing a cement-stabilized crushed stone mixed material with better performance and higher cost-effectiveness.

[0063] Example 1

[0064] A method for preparing a cement-stabilized crushed stone mixed material is as follows, in parts by weight:

[0065] Mix 80 parts of aggregate, 5 parts of cement, 20 parts of recycled fine aggregate, 2 parts of polycarboxylic acid water-reducing agent, 3 parts of modified reinforcing agent and 8 parts of water, and mix them in a vibrating mixer. The mixing time is 10 seconds, the amplitude of the vibrating shaft is 1 mm, and the rotation speed is 200 rad / s. Spread the mixture on the to-be-paved position, roll and compact it to form a base layer, cover the base layer with geotextile, sprinkle water every other day to keep the base layer moist, and maintain the base layer for 10 days to obtain a mixed material.

[0066] The aggregate is prepared by mixing limestone, basalt and recycled coarse aggregate in a mass ratio of 2:1:4, and the recycled coarse aggregate is obtained by crushing stone processing waste and passing through a 10-mesh sieve.

[0067] The recycled fine aggregate is crushed concrete or bricks, which is obtained by crushing and sieving through a 100-mesh sieve.

[0068] The preparation method of the modified enhancer is as follows:

[0069] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of ethylene glycol dimethacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0070] S2: Add 16 kg of fumaramide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0071] Example 2

[0072] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0073] The preparation method of the modified enhancer is as follows:

[0074] S1: 1 kg of acrylonitrile and 6 kg of ethylene glycol dimethacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0075] S2: Add 16 kg of fumaramide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0076] Example 3

[0077] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0078] The preparation method of the modified enhancer is as follows:

[0079] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of glycidyl methacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0080] S2: Add 16 kg of fumaramide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0081] Example 4

[0082] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0083] The preparation method of the modified enhancer is as follows:

[0084] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of methyl 2-(hydroxymethyl)acrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0085] S2: Add 16 kg of fumaramide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0086] Example 5

[0087] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0088] The preparation method of the modified enhancer is as follows:

[0089] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of methyl methacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0090] S2: Add 16 kg of fumaramide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0091] Example 6

[0092] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0093] The preparation method of the modified enhancer is as follows:

[0094] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of ethylene glycol dimethacrylate were mixed and added to 15 kg of acryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0095] S2: Add 16 kg of fumaramide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0096] Example 7

[0097] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0098] The preparation method of the modified enhancer is as follows:

[0099] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of ethylene glycol dimethacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0100] S2: Add 16 kg of cinnamamide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; use acetone to wash the reactant to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0101] Example 8

[0102] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0103] The preparation method of the modified enhancer is as follows:

[0104] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of ethylene glycol dimethacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0105] S2: Add 16 kg of methacrylamide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; use acetone to wash the reactant to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0106] Example 9

[0107] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0108] The preparation method of the modified enhancer is as follows:

[0109] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of ethylene glycol dimethacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0110] S2: Add 16 kg of 4-chlorocinnamamide and 80 kg of water to the pretreated product obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0111] Example 10

[0112] The preparation method of a cement-stabilized crushed stone mixed material is basically the same as that of Example 1, the only difference being the preparation method of the modifying enhancer.

[0113] The preparation method of the modified enhancer is as follows:

[0114] S1: 1 kg of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 6 kg of ethylene glycol dimethacrylate were mixed and added to 15 kg of 2-fluoroacryloyl chloride, nitrogen was introduced to replace the air in the reaction system, 0.12 kg of benzoyl peroxide was added, and the mixture was heated to 80° C. and reacted for 2 hours to obtain a pretreated product;

[0115] S2: Add 16 kg of acrylamide and 80 kg of water to the pretreated material obtained in step S1, introduce nitrogen again to fully replace the air in the reaction system, add 0.12 kg of benzoyl peroxide, and react at 80° C. for 5 hours to obtain a reactant; wash the reactant with acetone to remove impurities and unreacted raw materials to obtain a modified enhancer.

[0116] Comparative Example 1

[0117] A method for preparing a cement-stabilized crushed stone mixed material is as follows, in parts by weight:

[0118] Mix 80 parts of aggregate, 5 parts of cement, 20 parts of recycled fine aggregate, 2 parts of polycarboxylic acid water-reducing agent and 8 parts of water, and mix them in a vibrating mixer. The mixing time is 10 seconds, the amplitude of the vibrating shaft is 1 mm, and the rotation speed is 200 rad / s. Spread the mixture on the to-be-paved position, roll and compact it to form a base layer, cover the base layer with geotextile, sprinkle water every other day to keep the base layer moist, and cure the base layer for 10 days to obtain a mixed material.

[0119] The aggregate is prepared by mixing limestone aggregate, basalt aggregate and recycled coarse aggregate in a mass ratio of 2:1:4, and the recycled coarse aggregate is obtained by crushing stone processing waste and passing through a 10-mesh sieve.

[0120] The recycled fine aggregate is crushed concrete or bricks, which is obtained by crushing and sieving through a 100-mesh sieve.

[0121] Test Example 1

[0122] The drying shrinkage test of the mixed materials prepared in the embodiments of the present invention and the comparative examples was carried out according to the relevant provisions of JTS / T 236-2019 "Technical Specifications for Testing and Detection of Concrete in Water Transport Engineering". Each group was tested 3 times and the average value was taken; the test results are shown in Table 1.

[0123] Table 1

[0124]

[0125]

[0126] Test Example 2

[0127] Mechanical properties test

[0128] The compressive strength and splitting strength tests of the mixed materials prepared in the embodiments of the present invention and the comparative examples were conducted in accordance with the relevant provisions of JTS / T 236-2019 "Technical Specifications for Testing and Detection of Concrete in Water Transport Engineering - Test Procedures for Concrete in Water Transport Engineering". Tests on the compressive strength and splitting strength of concrete were conducted. The test results are shown in Table 2.

[0129] Table 2

[0130] Experimental protocol Compressive strength(MPa) Splitting strength(MPa) Example 1 6.92 0.64 Example 2 6.43 0.55 Example 3 6.65 0.61 Example 4 6.57 0.60 Example 5 6.50 0.59 Example 6 6.66 0.61 Example 7 6.54 0.60 Example 8 6.57 0.60 Example 9 6.51 0.58 Example 10 6.44 0.57 Comparative Example 1 6.10 0.50

[0131] It can be seen from test examples 1 to 2 that the mixed material obtained in Example 1 of the present invention has a smaller average shrinkage coefficient and greater compressive strength and splitting strength.

[0132] From the perspective of molecular structure, the differences between 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and acrylonitrile may affect their chemical reactivity in modified reinforcing agents and the performance of the final product. Acrylonitrile is a simple unsaturated nitrile with moderate polarity. 1-allyl-1,4-dihydro-3-pyridinecarbonitrile contains allyl and pyridine rings, which increase the polarity of the molecule and may promote the interaction with cement hydration products, thereby improving the bonding force. The pyridine ring generally has good chemical stability, which may help improve the long-term performance of the modified reinforcing agent in cement-based materials. The molecular structure of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile is more complex than that of acrylonitrile, with more functional groups and a larger conjugated system. This structure may help to form more cross-linking and network structures, increasing the cohesion of the material. The presence of allyl groups may provide a certain plasticizing effect for the modified reinforcing agent, which helps to improve the flexibility of cement-based materials, thereby reducing the shrinkage coefficient to a certain extent. In summary, the molecular structure characteristics of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile may improve the performance of cement-stabilized crushed stone mixtures in many ways, including enhanced adhesion, improved compatibility, increased chemical stability, and reduced water absorption. These factors work together to lead to lower shrinkage coefficients and higher mechanical properties.

[0133] Example 1 is compared with Examples 2 to 5. The ethylene glycol dimethacrylate used in Example 1 is a commonly used cross-linking monomer with two methacrylate groups, which can form a highly cross-linked network structure. The ethylene glycol chain provides a certain flexibility, which helps to relieve internal stress and reduce the shrinkage of the material. The glycidyl methacrylate in Example 3 contains glycidyl groups, which can provide more hydrogen bonding sites and may increase the rigidity of the network. However, excessive cross-linking may increase the shrinkage coefficient to a certain extent. The 2-(hydroxymethyl) methyl acrylate in Example 4 provides hydroxymethyl groups, which may help to form additional hydrogen bonds with cement hydration products. However, compared with ethylene glycol dimethacrylate, the network formed may not be uniform enough or the cross-linking density is not high enough, which may affect its performance. The methyl methacrylate in Example 5 is a simple methacrylate monomer, and the polymer network formed may be softer but not rigid enough. This may result in lower compressive strength and splitting strength. The use of ethylene glycol dimethacrylate in Example 1 may provide an optimal balance between cross-linking density and flexibility, resulting in a lower shrinkage coefficient and higher mechanical properties. The introduction of ethylene glycol chains may help introduce segmental motion in the network, reduce internal stress concentration, and thus reduce shrinkage. At the same time, the highly cross-linked nature of ethylene glycol dimethacrylate helps to improve compressive strength and splitting strength.

[0134] When comparing Example 1 and Example 6, the only difference between the two is that different acyl chloride compounds are used: Example 1 uses 2-fluoroacryloyl chloride, while Example 6 uses acryloyl chloride. The following is an analysis of the possible effects of these two compounds on the performance of cement-stabilized macadam mixed materials from the perspective of molecular structure: 2-fluoroacryloyl chloride contains a fluorine atom that replaces a hydrogen atom in acryloyl chloride. The use of 2-fluoroacryloyl chloride may have a positive impact on the performance of cement-stabilized macadam mixed materials by increasing reaction activity, changing polymer chain structure, enhancing interaction with cement, reducing drying shrinkage, improving mechanical properties and increasing chemical stability. These factors work together and may result in the mixed material obtained in Example 1 having a smaller average shrinkage coefficient and greater compressive strength and splitting strength.

[0135] The amide monomers used in Example 1 and Examples 7 to 10 are different. The fumaramide used in Example 1 contains two unsaturated dicarbonyl groups (C=O), two amino groups and a double bond (C=C), which enables it to participate in Michael addition reactions and other types of polymerization reactions. The unsaturated double bonds of fumaramide may promote copolymerization with other monomers to form a more uniform and stable polymer network. Fumaramide may help to form more cross-linking points, thereby improving the cohesion and mechanical properties of the mixed material. Fumaramide may have better compatibility with cement hydration products, which helps to improve adhesion and overall performance. In contrast, other amide monomers may exhibit different reactivity and compatibility in the polymer network due to their structural characteristics, thereby affecting the final shrinkage coefficient, compressive strength and splitting strength. For example, the benzene rings of cinnamamide and 4-chlorocinnamamide may increase the π-π interaction between molecules, thereby affecting the performance of the mixed material; while the simple structure of acrylamide may not be sufficient to provide enough cross-linking points, thereby affecting the mechanical properties of the material.

Claims

1. A method for preparing a cement-stabilized crushed stone mixed material, characterized in that: Here’s how: Aggregate, cement, recycled fine aggregate, polycarboxylate water-reducing agent, modified reinforcing agent and water are mixed and stirred in a vibrating mixer, the mixed material is spread on the location to be paved, rolled and compacted to form a base, the base is covered with a geotextile, water is sprinkled every other day to keep the base moist, and the base is cured to obtain a mixed material; The weight proportions of the components are 70-90 parts of aggregate, 4-6 parts of cement, 15-25 parts of recycled fine aggregate, 1-3 parts of polycarboxylate water reducer, 2-4 parts of modifier and enhancer, and 6-10 parts of water; The preparation method of the modified reinforcing agent is as follows, in parts by weight: S1: 0.5-2 parts of 1-allyl-1,4-dihydro-3-pyridinecarbonitrile and 5-7 parts of ethylene glycol dimethacrylate are mixed and added to 13-17 parts of 2-fluoroacryloyl chloride, nitrogen is introduced to replace the air in the reaction system, 0.08-0.15 parts of initiator are added, and the mixture is heated to 70-90° C. and reacted for 1-3 hours to obtain a pretreated product; S2: adding 15-17 parts of fumaramide and 70-90 parts of water to the pretreated product obtained in step S1, introducing nitrogen again to fully replace the air in the reaction system, adding 0.08-0.15 parts of initiator, and reacting at 70-90° C. for 4-6 hours to obtain a reactant; washing the reactant with an organic solvent to remove impurities and unreacted raw materials to obtain a modified enhancer; The aggregate is made of limestone, basalt and recycled coarse aggregate in a mass ratio of 1-3:0.5-2:3-5, and the recycled coarse aggregate is obtained by crushing stone processing waste and passing through a 5-20 mesh sieve; The recycled fine aggregate is crushed concrete or bricks, which is obtained by crushing and screening through a 50-200 mesh sieve.

2. The method for preparing a cement-stabilized crushed stone mixed material according to claim 1, characterized in that: The mixing time is 5 to 15 seconds, the amplitude of the vibration shaft is 0.5 to 2 mm, and the rotation speed is 150 to 250 rad / s.

3. The method for preparing a cement-stabilized crushed stone mixed material according to claim 1, characterized in that: The curing time is 7 to 15 days.

4. The method for preparing a cement-stabilized crushed stone mixed material according to claim 1, characterized in that: The initiator is benzoyl peroxide.

5. The method for preparing a cement-stabilized crushed stone mixed material according to claim 1, characterized in that: The organic solvent is one of acetone, anhydrous ethanol and N,N-dimethylacetamide.

6. A cement-stabilized crushed stone mixed material, characterized in that: The method is prepared according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-filled, high-resilience, soft foamed polyethylene material with calcium carbonate and its preparation method

    CN103408823B

  • Low-Tg acrylate emulsion for cement-based building materials, and preparation method thereof

    CN104530304A

  • In-situ synergistic modified reinforced cement-based composite material and application thereof

    CN114436597A